PENGARUH IKLIM, KULTUR, DAN KINERJA STRUKTUR ORGANISASI TERHADAP MUTU PENDIDIKAN DI SMP NEGERI 1 HAMPARAN PERAK - Amini Amini; Irvan Irvan; Kurnia Putri (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
This study aims to determine how the influence of the variables in the study model, named clime, culture and organizational structure performance on the quality of education in SMP Negeri 1 Hamparan Perak. This research took place at SMP Negeri 1 Hamparan Perak which was carried out from November 2020-March 2021. The research population was all 62 educators, teachers and school principals and the sample used was 62 people from the total population in SMP Negeri 1 Hamparan Perak. In this study, the instrument used to obtain data and information about the object of research was using a questionnaire with a Likert scale approach. The analysis used is path analysis. From the results of the research data analysis shows that the influence of clime, culture, and structure performance variables on the quality of education is 0.749 or the equivalent of 74.9% is significant at the significant level of 0.0 Furthermore, the results of the study show that the influence of organizational clime variables on the quality of education shows that there is a significant influences. a significant amount is 3,531. Then the result of the influence of organizational culture variables on the quality of education showed a significant effect of 2.53. And the results of the study shows that the effect of the organizational structure performance variables on the quality of education showing a significant influence of 4.33